Killing fields, living fields an unfinished portrait of the Cambodian church - the church that would not die - Cormack, Don; Overseas Missionary Fellowship; China Inland Mission (East Sussex, U.K. Monarch, 1997)
Includes index
Keywords: Church history -- Cambodia